The genus Tetralicia Harrison (Hemiptera: Sternorrhyncha: Aleyrodidae) in California, U.S.A., with the description of five new species and a redescription of Tetralicia granulata Sampson & Drews, 1941 - Ellenrieder, Natalia Von; Gill, Raymond J. (Zootaxa, 2024)
Nineteen species of Tetralicia Harrison are recorded from California, United States of America, of which five are new to science and are described here: Tetralicia agrifoliae sp. nov., T. guajavae sp. nov., T. hoelmeri sp. nov., T. lantanae sp. nov., and T. salsolae sp. nov., and four are new records for the State: T. abnormis (Quaintance, 1900), T. eriogonum (Carapia-Ruiz, 2020), T. mexicana (Carapia Ruiz & Sánchez Flores in Carapia Ruiz, Sánchez Flores, García Martínez & Castillo Gutiérrez, 2018), and T. nevadensis (Dooley in Dooley, Lambrecht & Honda, 2010). Neotypes are designated for California species for which types were not designated originally and for which type material is apparently lost: Aleuropleurocelus acaudatus Drews & Sampson, 1958, A. coachellensis Drews & Sampson, 1958, A. laingi Drews & Sampson, 1956, A. oblanceolatus Drews & Sampson, 1958, and A. ornatus Drews & Sampson, 1958. All Tetralicia species found in California are keyed, fully illustrated, measured, and accompanied by species accounts based on their puparia including characterization, diagnosis, hosts, and distribution. Tetralicia granulata Sampson & Drews, 1941 is redescribed based on its type material, and it is believed to be currently known only from its type series from Mexico. The earlier nymphal instars of four species (T. guajavae, T. hoelmeri, T. hyptisemoryi, and T. lantanae) and the adults of three species (T. guajavae, T. hoelmeri, and T. lantanae) are described, illustrated, and diagnosed from known congeners.